'Inpatriation' for knowledge-transfer within Japanese multinational corporations. Issue 4 (8th August 2017) - Murakami, Yukiko
Abstract: This article uses knowledge management theory and the gravity model to analyse the determinants of 'inpatriation' for knowledge-transfer within multinational corporations (MNCs) and the differences in their effects based on the region of the subsidiary's host country. The empirical analysis uses data collected through a survey of the overseas subsidiaries of Japanese MNCs and finds that factors related to both the countries and the individual MNCs affect inpatriation, with the former factors having a stronger influence than the latter. With regard to the country factors, a smaller geographic distance and a larger cultural distance between the home and host countries and a lower GDP per capita in the subsidiary's host country increase inpatriation. Regarding the individual MNC factors, a larger subsidiary R&D budget, a larger parent firm and the execution of collaborative R&D projects between a subsidiary and its parent firm increase inpatriation. Additionally, this study finds that in Asia, geographic closeness and low GDP per capita facilitate inpatriation, whereas a relatively small R&D budget and rare collaborative R&D projects with Japan decrease inpatriation. More subsidiaries in Asia send inpatriates to Japan than do subsidiaries in other regions because these positive factors are much stronger than these negative factors.